2005
DOI: 10.1016/j.ijepes.2004.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and optimisation of renewable energy systems

Abstract: Renewable energy systems are still much more expensive than traditional grid connected power, except in remote areas. Thus it is important that designs be optimised to achieve the least delivered energy cost over a lifetime of 20 years or so. This paper shows that to achieve grid level of reliability with wind solar and storage units alone is impossibly expensive so practical designs have always incorporated standby generation of some sort or other. This paper describes a simulation technique that enables a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…PV panels generated power changes throughout the year. Figures 1 and 2 show the average hourly solar distribution, and the electrical loading for residential customers [1,2]. It is clearly shown that the generated power requires energy storage to support the house daily (24 hours period) electrical consumptions.…”
Section: Theoretical Studymentioning
confidence: 99%
See 1 more Smart Citation
“…PV panels generated power changes throughout the year. Figures 1 and 2 show the average hourly solar distribution, and the electrical loading for residential customers [1,2]. It is clearly shown that the generated power requires energy storage to support the house daily (24 hours period) electrical consumptions.…”
Section: Theoretical Studymentioning
confidence: 99%
“…Taking into consideration the fact that PV micro-grid produces maximum power during the midday period on a sunny day. The house peak demands hours are located in the morning and late in the afternoon/evening [1,2]. Based on the mentioned information, the micro-grid generated power doesn't support the house critical electrical requirements.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a number of optimization modeling methods were proposed for supporting the management of GHG emission mitigation particularly through the adoption of renewable energies [54,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143]. In the middle of the 1970s, Duff (1975) presented an optimization model to design solar thermal energy systems in accordance with the minimum system cost [144].…”
Section: Optimization Of Ghg Emission Mitigationmentioning
confidence: 99%
“…With flexible operational mode and environment-friendly features, more and more distributed generations are integrated into the distribution network, which brings benefit on the carbon reduction of distribution system [20]. As two basic methods of loss of expected energy (LOEE) for the distribution system with DG, the studies of analytical method [21][22][23][24][25][26][27][28][29] and Monte Carlo method [30][31][32][33][34][35][36] have made some progress. These studies indicate that the adoption of DG is actually equals to increasing the number and capacity of the backup of distribution system, thus improving the carbon reduction of the distribution system.…”
Section: Introductionmentioning
confidence: 99%